Dasyproctus yesudasi sp. nov. (Hymenoptera, Crabronidae, Crabroninae), a new square-headed moustache wasp from south India - Binoy, C.; Kumar, P. Girish (Zootaxa, 2024)
Dasyproctus yesudasi sp. nov. is newly described from south India. Illustrations and comparisons with its congeners are provided. Type specimens of five species, viz., D. oppidanus Leclercq, 1972, D. idrieus (Cameron, 1901), D. opifex (Bingham, 1897), D. orientalis (Cameron, 1890), and D. pulveris (Nurse, 1902) are illustrated for the first time. Diagnoses of D. pentheri, D. oppidanus and D. opifex are provided based on images of museum specimens, and an updated key to Indian species is provided.